LEGAL PERSPECTIVES ON MORAL HAZARD: STRENGTHENING DEMOCRACY IN INDONESIA’S POLITICAL SYSTEM - Ristyawati, Aprista (Doctoral of Law Program, Faculty of Law, Universitas Diponegoro, 2025)
Political parties are central to the democratic system in Indonesia, acting as the intermediary between citizens and the government. However, one of the most significant challenges facing political parties today is the issue of moral hazard, which occurs when party members prioritize personal or group interests over the public good. This study explores the impact of moral hazard within political parties and its detrimental effects on democracy in Indonesia. Using doctrinal legal research with a conceptual and descriptive analysis of secondary data, the study finds that moral hazard leads to a decline in public trust, diminished political participation, and weakened social control. The consequences also extend to the quality of public policies, which suffer due to misaligned priorities, lack of expertise, and insufficient evaluation. Moreover, moral hazard erodes accountability, which fuels corruption, nepotism, and a lack of oversight, ultimately compromising the quality of democracy. To address these challenges, the study proposes a multi-pronged strategy, including strengthening internal oversight within political parties, improving transparency, and reforming the party system. Key reforms include ensuring ethical conduct through codes of ethics, establishing independent oversight committees, and protecting whistleblowers. The study also advocates for stricter legal enforcement, increased public participation, and the role of media in holding parties accountable. Finally, global cooperation is crucial in tackling cross-border corruption and unethical practices. By implementing these reforms, Indonesia can reduce moral hazard within political parties, strengthening the democratic process and ensuring that the political system serves the public interest effectively and transparently.